Genetic variability and antimicrobial resistance profile of Malaysian M. gallisepticum and M. synoviae poultry isolates - Taiyari, H.; Zakaria, Zunita; Abu, J.; Faiz, N.M. (Fundacao APINCO de Ciencia e Tecnologia Avicolas, 2024)
M. gallisepticum (MG) and M. synoviae (MS) infections are among the most common and complicated respiratory diseases in birds. The infections can cause a huge loss of production performance in different types of poultry farming, including broilers and layers. Avian mycoplasmosis in Malaysia was detected many years ago, but there is a paucity of information on its genetic variability and antimicrobial susceptibility profile. Therefore, this study was carried out to isolate, molecular characterize, and determine the antimicrobial minimum inhibitory concentration of Malaysian MG and MS poultry isolates. A total of 492 choanal swab samples were collected from different poultry farms and subjected to isolation and PCR. Using immunofluorescence assay, 36.4% (179/492) MG and MS isolates were detected, out of which 26.8% (48/179) samples yielded MG colonies, and 73.2% (131/179) samples yielded MS colonies. Using PCR, a higher number of MG and MS were detected. M. gallisepticum was detected in 28% (138/492) of samples, while 61.2% (301/492) of samples were positive by PCR for MS. Phylogenetic analysis of the MG local isolates showed an identical pattern in both pvpA and mgc2 genes with MG strain F. M. synoviae field isolates shared an identical pattern of vlhA gene with the MS strain MS-H. The isolates had the highest resistance to erythromycin, lincomycin, and chlortetracycline. The high number of positive MG and MS infections is suggestive of the continuous circulation of these pathogens among poultry in Malaysia. Therefore, continuous monitoring of the susceptibility profile of isolates to ensure effective treatment dosage is highly recommended.